Bridging Policy and Practice: Reforming Indonesia’s Creative Economy Framework for Music and Visual Arts - Mohamed, Sheik (Indonesian Scientific Publication, 2024)
Indonesia's creative economy contributed approximately 7.44% to national GDP by 2022, with fashion, culinary, and crafts as leading sectors. However, music and visual arts remain underrepresented despite their cultural significance and growth potential. This article investigates policy and implementation gaps that hinder the inclusion of these sectors, focusing on legal, financial, and infrastructural dimensions. Employing a qualitative policy analysis approach, the study draws on regulatory documents (e.g., UU 24/2019, PP 24/2022), statistical reports, and program data from 2022–2024. The research identifies key barriers such as inconsistent regional application of national policies, lack of operational SOPs for IP valuation, limited access to creative financing, and systemic royalty management issues. Findings indicate that while regulatory support exists, it often fails to translate into practical benefits for music and visual arts stakeholders. Royalty distribution remains opaque and underutilized; creative financing tools are constrained by valuation and administrative gaps; and export initiatives rarely prioritize intangible cultural products. Rural areas face compounded challenges due to weak outreach and infrastructure. To ensure inclusivity, the upcoming 2026–2035 Creative Economy Masterplan must adopt broader metrics beyond GDP encompassing cultural participation, regional equity, and digital engagement. Institutional coordination, transparent governance, and grassroots empowerment are critical to aligning national ambitions with ground level realities.